Ecosystems Services from Community Forestry: Prospects and Challenges for Improving Local Livelihoods in Nepal - Ojha, H.; Paudel, N.S.; Timsina, J.; Chaudhary, S.; Baral, H. (Springer, 2022)
Nepal’s community forestry is touted as a development success, especially in relation to how local community groups can be empowered by the state to conserve and manage communal forest areas for local livelihoods improvements. However, this success is limited in relation to the production and supply of conventional forest products or a narrow range of ecosystem services (ES). The concept of ES has recently landed in Nepal’s policy domain and an evolving body of research has also highlighted the potential of applying ES in community forestry for augmenting livelihoods improvements, climate change adaptation and mitigation, and biodiversity conservation. Yet, there is still a lack of evidence on the degree to which community forest user groups are expanding their forest management practices by including additional range of ES. Drawing on 14 case studies of community forests from across the country, as well as a recent review of literature and analysis of secondary data, this chapter assesses the potential of an ecosystem centred approach to community forest management for local community livelihoods in Nepal. We identify a variety of emerging initiatives towards ES-based management of community forests, demonstrating the need for a strategic shift away from the narrowly focused, subsistence-oriented forest management to a more holistic management of forest ES. We also identify priority challenges that need to be tackled in facilitating this shift to achieve the sustainable production of ES for livelihoods improvements and its contribution towards climate change mitigation and sustainable development goals.